Human Resource Management Strategies in Increasing Employee Engagement in the Service Sector - Arif, Siti Afnan (Maroon Journal De Management, 2024)
This study aims to analyze the green supply chain management (GSCM) strategies implemented by retail companies and the challenges faced in their implementation. The method used is a survey with structured interviews with several respondents who have important roles in the company's supply chain. This study focuses on strategies such as green procurement, route optimization, use of renewable energy, recycling management, and marketing of environmentally friendly products. The results of the study indicate that the GSCM strategies implemented have had a positive impact on reducing operational costs and improving the company's image, although there are challenges such as high initial investment costs and limited green logistics infrastructure. The recommendations of this study include the need for government support in the form of tax incentives and investment in environmentally friendly technologies as well as closer collaboration with suppliers to improve sustainability.